Evaluatıon Of Cranıal Base Morphology Of Indıvıduals Wıth Skeletal Class II Anomaly - M. Özgür Sayın; Hakan Türkkahraman (Galenos Yayinevi, 2004)
The aim of this study was to find out if individuals with skeletal Class II anomaly had specific cranial base configurations. The material of the study was composed of lateral cephalograms of 64 subjects. Subjects with ANB angle between 0-4 degrees were included in the Class I group (16 females, 16 males) and patients with ANB angle > 4 degrees were included in the Class II group (16 females, 16 males). Comparison of the groups were performed by using independent samples t-test. Correlations between ANB angle and cranial base measurements were calculated by using Pearson correlations. Cranial base angle and anterior and posterior cranial base lengths showed no significant difference between the groups. No significant correlations were found between ANB angle and cranial base angle, posterior cranial length. ANB angle was directly correlated with anterior cranial length (p<0,05). However this was not significant clinically. As a result, there was no significant difference in cranial base configurations between Class I and Class II patients.